Ecosystem shifts in Alpine streams under glacier retreat and rock glacier thaw: A review - Brighenti, Stefano; Tolotti M.; Bruno M. C.; Wharton G.; Pusch M. T.; Bertoldi W. (Science of The Total Environment, 2019)
This review provides a detailed synthesis of the effects of glacier retreat and permafrost thaw on stream ecosystems in the European Alps. As a working framework, we present a conceptual model developed from an integration of current knowledge and understanding of the habitat and ecological shifts in Alpine streams caused by deglaciation. In our work, we depict how climate change and the loss of cryosphere trigger complex cascading effects on Alpine hydrology, as the main water sources shift from snow and glaciers to rock glaciers, groundwater, and precipitation. The associated changes in habitat conditions, such as channel stability, turbidity, temperature, nutrient loadings, and concentrations of legacy pollutants and trace elements are identified. These changes are followed by complex ecological shifts in the stream communities (microbial community, primary producers, invertebrates) and food webs, with a predicted loss of biotic diversity. Corresponding increases in taxa abundances, biomass, functional diversity, and in the complexity of food webs, are predicted to occur in the upper reaches of Alpine catchments in response to ameliorating climatic and habitat conditions. Finally, current knowledge gaps are highlighted as a basis for framing future research agendas. In particular, we call for an improved understanding of permafrost influence on Alpine headwaters, including the ecology of rock-glacier fed streams, as these streams are likely to become increasingly important for water supply in many glacier-free Alpine valleys in the near future.